The effects of acute exercise on arterial endothelial diameter: A meta-analysis - Briceño Torres, José Miguel (2018)
There is abundant literature regarding the chronic effects of different exercise modalities on arterial diameter and endothelial function; however, there is a dearth of information related to the acute effects. We investigated the acute effects of different exercise modalities on arterial endothelium diameter as measured by flow-mediated dilation (FMD). An electronic search was performed in electronic databases using the following word combinations: “acute exercise”, “FMD”, “endothelial function”, “exercise”, “vascular endothelium”, and “flow-mediated dilation”. The inclusion criteria were experimental studies with single session treatment, studies in healthy human adults, English language publications, and studies reporting pre- and post- flow-FMD measures. The random effects model was used to calculate effect sizes (ES). We included 13 studies (43 effect sizes), representing 378 participants (245 men and 133 women). Twelve studies had poor and very poor quality. Aerobic exercise showed a small effect (ES = 0.27, CI95% = -0.08, 0.62, p = 0.11), resistance training a trivial effect (ES = -0.15, CI95% = -0.76, 0.46, p = 0.25), and interval exercise a small effect (ES = 0.23, CI95% = -0.82, 1.27, p = 0.15) on arterial diameter. In conclusion, aerobic, resistance, and interval training exercises did not elicit a positive arterial diameter acute response. These findings are influenced by the poor methodological quality of the literature.